Dynamics of oxygen supply and consumption during mainstream large-scale composting in China. (November 2016) - Zeng, Jianfei; Shen, Xiuli; Han, Lujia; Huang, Guangqun
Highlights: Oxygen uptake rate, free air space and some basic parameters were investigated. A long active phase, low maximum temperature and high pore CH4 content were observed. Pore O2 content maintained <5% for more than 42 days (89%) of the whole period. The daily percentage of time under aerobic conditions was <14% of a single day. Abstract: This study characterized some physicochemical and biological parameters to systematically evaluate the dynamics of oxygen supply and consumption during large-scale trough composting in China. The results showed that long active phases, low maximum temperatures, low organic matter losses and high pore methane concentrations were observed in different composting layers. Pore oxygen concentrations in the top, middle and bottom layers maintained <5 vol.% for 40, 42 and 45 days, respectively, which accounted for more than 89% of the whole period. After each mechanical turning, oxygen was consumed at a stable respiration rate to a concentration of 5 vol.% in no more than 99 min and remained anaerobic in the subsequent static condition. The daily percentage of time under aerobic condition was no more than 14% of a single day. Therefore, improving FAS, adjusting aeration interval or combining turning with forced aeration was suggested to provide sufficient oxygen during composting.